2018
DOI: 10.31729/jnma.3340
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-radiological Observations in Meconium Aspiration Syndrome

Abstract: Introduction: To understand and report the prevalence of meconium aspiration syndrome and the clinico-radiological features in a tertiary care hospital of western Nepal. Methods: An observational study carried out for a year in 2014-15 in all babies with MAS. Clinical and radiological profiles of MAS in relation to gender, gestational age, mode of delivery, birth weight, Apgar score, thickness of meconium, age at admission and the immediate outcome were studied. Results: Out of 584 admitted newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
5
0
2
Order By: Relevance
“…Although numerous studies have reported no significant differences in adverse neonatal outcomes associated with meconium consistency [ 52 , 74 , 75 , 76 ], our clinical experience [ 77 ], and the results of this retrospective analysis suggest that thick meconium may serve as a clinical risk for adverse neonatal outcomes, including low APGAR scores at 1 min and 5 min, neonatal death, or the need for NICU admission, resuscitation, CPAP use, or ventilator use. Our findings agree with the results of several papers [ 4 , 21 , 22 , 78 , 79 , 80 ]. Maternal factors, including maternal age, delivery mode, and the presence of medical conditions such as preeclampsia, diabetes, antepartum hemorrhage, PROM, polyhydramnios and oligohydramnios, and neonatal factors including gestational age, birth weight, sex of the infant, and the prevalence of hypoglycemia have all been reported to be associated with the presence of MSAF [ 14 , 21 , 22 , 25 , 78 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although numerous studies have reported no significant differences in adverse neonatal outcomes associated with meconium consistency [ 52 , 74 , 75 , 76 ], our clinical experience [ 77 ], and the results of this retrospective analysis suggest that thick meconium may serve as a clinical risk for adverse neonatal outcomes, including low APGAR scores at 1 min and 5 min, neonatal death, or the need for NICU admission, resuscitation, CPAP use, or ventilator use. Our findings agree with the results of several papers [ 4 , 21 , 22 , 78 , 79 , 80 ]. Maternal factors, including maternal age, delivery mode, and the presence of medical conditions such as preeclampsia, diabetes, antepartum hemorrhage, PROM, polyhydramnios and oligohydramnios, and neonatal factors including gestational age, birth weight, sex of the infant, and the prevalence of hypoglycemia have all been reported to be associated with the presence of MSAF [ 14 , 21 , 22 , 25 , 78 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Discussionsupporting
confidence: 93%
“…3 Caesarean section was very commonly done in MSAF cases and it accounted for 49.09% cases as compared to 25.79% cases in control group, rates being nearly double and difference being statistically significant in the study of Rajlaxmi et al 8 Lama et al also concluded higher rates of MAS in babies born through LSCS. 12 Naveen also concluded that chances of LSCS were more in MSAF babies. 13 The highest incidence of MAS was found in gestational age of 39-40 weeks 57.3% followed by 37-38 weeks in 25%.…”
Section: Discussionmentioning
confidence: 98%
“…За даними різних авторів, наявність меконію в навколоплідних водах спостерігається у 10-24 % всіх пологів [1,2,3,4,5,6]. Частота виявлення меконію у навколоплідних водах у 6 разів вища серед жінок з терміном вагітності 42 тижнів або більше порівняно з терміном 37 тижнів.…”
Section: вступunclassified